Macrocyclic peptides derived from AcPHF6*and AcPHF6 to selectively modulate the Tau aggregation - Dangi, Abha; Qureshi, Tazeen; Chinnathambi, Subashchandrabose; Marelli, Udaya Kiran (Bioorganic Chemistry, 2024)
Ten macrocyclic peptides, each comprising 14 amino acids, were designed and synthesized based on the Tau aggregation model hexapeptides AcPHF6* and AcPHF6. The design took into account the aggregation tendencies of each residue in AcPHF6* and AcPHF6, their aggregation models, while employing peptide-based structural design principles including N-methylation to promote turns and to block hydrogen bond propagation and elongation of the aggregation chain. NMR analysis supported that all these peptides adopted an antiparallel beta-sheet conformation. Self-aggregation studies characterized the aggregation properties of these peptides, identifying two peptides with the highest (P3) and lowest (P8) aggregation tendencies. In cross-aggregation studies with the parent peptides AcPHF6* and AcPHF6, P3 and P8 were found to promote and reduce aggregation, respectively. Furthermore, P3 and P8 demonstrated an enhancement and diminution effect on the aggregation of K18wt, indicating their capacity to modulate aggregation even at the macromolecular level. Thus, the two simple peptides, P3 and P8 selectively exhibit pro- or anti-aggregation effects on PHF peptides and Tau. This study, has thus developed structurally well-defined non-complex peptides, derived from AcPHF6* and AcPHF6, to modulate Tau aggregation as desired, offering applications in Tau model studies and the development of Tau aggregation inhibitors or promoters.
Keywords: Cyclic peptides; Peptide -based drug design (PBDD); Peptide conformation; PHF peptides; Tau Aggregation